1988
DOI: 10.1159/000167578
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Uremic Hyperphosphatemia -Is There Still a Need for Aluminum Salts?

Abstract: Aluminum-containing phosphate binders have been widely employed in the past in the management of uremic hyperphosphatemia. However, an increasing number of reports on aluminum toxicity has stimulated efforts to replace this therapy by safer methods. The aim of the present review is to critically evaluate other treatment strategies. It appears that aluminum-containing phosphate binders should no longer be considered the treatment of choice for controlling uremic hyperphosphatemia. Calcium carbonate, calcium cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Because of the toxic effects of aluminum [ 18] calcium salts have nowadays widely replaced aluminum hydrox ide as phosphate binders in patients with chronic renal failure. In addition to phosphate binding, calcium salts are useful in increasing the concentration of ionized cal cium of extracellular fluid, which is known to be the most important regulator of PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the toxic effects of aluminum [ 18] calcium salts have nowadays widely replaced aluminum hydrox ide as phosphate binders in patients with chronic renal failure. In addition to phosphate binding, calcium salts are useful in increasing the concentration of ionized cal cium of extracellular fluid, which is known to be the most important regulator of PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ionized calcium was significantly lower with calcium ketoglutarate than with calcium carbonate. Both drugs caused a reduction in plasma P i ,and there was no difference in plasma P i or PTH levels [87,88]. Some 29% of patients taking calcium ketoglutarate withdrew from the study due to gastrointestinal discomfort.…”
Section: Currently Available P I Bindersmentioning
confidence: 93%
“…It is also a potent inhibitor of hydroxyapatite crystal formation, the initial stage in calciumphosphate precipitation [107]. 3-Phosphocitric acid, another inhibitor of calcium-phosphate precipitation, has been shown to prevent renal calcifications and progression of renal failure in 5/6th nephrectomized rats fed a high-phosphorus diet [12,87,108]. The potential in vivo effect of PFA in preventing calcium-phosphate precipitation has not been investigated.…”
Section: The Need For Phosphate Inhibitorsmentioning
confidence: 99%
“…In addition to being alu minum-free, it has the potential advantage of causing less hypercalcemia than other cal cium-containing phosphate binders. No other clinical studies of calcium alginate have been published, although another group re ported it to be less effective than the initial studies suggested [4], Therefore, we compared the efficacy of calcium alginate to that of aluminum hydroxide in patients on hospital hemodialysis.…”
mentioning
confidence: 99%